Service with the Signal Corps : The Civil War Memoir of Captain Louis R. Fortescue - Fortescue, Louis R., 1838-1915 (Book collections on Project MUSE., 2015)
During the Civil War Major Albert J. Myer created a system for transmitting information the would revolutionize military communications and lead to the creation of the U.S. Army Signal Corps. The Signal Corps originally met with resistance, particularly from high-ranking Regular Army officers, but the men who serviced in the Corps took great pride in their duties and eventually succeeded in changing everyones opinion. This is Louis R. Fortescue's memoir that presents a unique look at the Corps and important insights into the war as a whole. "This book provides very informative and fascinating insight into the experiences of a Signal Corps officer of the Union Army." Steven J. Rausch, U.S. Army Signal Corps HIstorian.